Special aspects of medical care for cancer patients during COVID-19 pandemic - Pavlushenko, Mariia; Liubota, Roman; Vereshchako, Roman; Anikusko, Nikolay; Liubota, Irina (Archive of Oncology, 2021)
The biggest challenge for the World Health Organization today is the fight against the COVID-19 pandemic. The current situation prompted major adjustments in the system of cancer care. In this review, we investigate the aspects of cancer treatment and care during the pandemic, since in this setting oncological services face challenges in determining the feasibility of anticancer treatments while minimizing the risk of infection. Cancer patients are at a higher risk from COVID-19 disease. Therefore, oncological community is discussing on the priorities for providing cancer therapies and care and at the same time minimizing the risk of infection.